Main helicopter rotor trimming using computational fluid dynamics method in forward flight. (January 2018) - Ma, Yimin; Chen, Ming; Wang, Qiang; Wang, Fang
In this paper, a computational fluid dynamics trimming method is proposed and compared with wind tunnel experiment and the blade element method. The NASA's generic ROBIN helicopter model is adopted for transient simulations to obtain the final main rotor trimming conditions. Totally three steps were applied to the computational fluid dynamics method. The first step is associated with no cyclic pitch motion, the second is regarding pure longitudinal cyclic pitch motion and the last is concerning with pure lateral cyclic pitch motion. At the same time, a simple linear equation system between the roll and pitching moment was established to get the final longitudinal and lateral cyclic pitch angles for the main rotor through the above three steps. An overset grid approach was used where the volume around each blade was modeled in an individual overset grid region. The rotor rotation was resolved with three degrees per time-step. Turbulence was modeled with the well-known SST K-omega model with second-order convection. The helicopter was in straight forward flight with an advance ratio ofμ = 0 . 151 . Three sources of stick angles, which are also called rotor trimming angles, were shown and compared with each other. And the corresponding results were also plotted with a type of history plot in the computational fluid dynamics condition. In the simulations, the results became quasi periodic after about 1.5 rotations and four rotor rotations were simulated for each case. The pitch moment coefficient and roll moment coefficient were all trimmed to about zero by the computational fluid dynamics trimming method while moments were not removed thoroughly in the other two source conditions.